LIDAH DAN HATI (SEBUAH ANALISA DALAM KONTEKS TERMINOLOGI AL-QUR’AN) - Umar Latif (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2016)
Many issues related to human structure and anatomy can be found in Al-Quran, and one of them is with regard to sense. Simply, there are some senses discussed in Al-Quran. According to Al-Quran, human sense consists of three parts, those are physical, inner, and heart senses. Even Al-Quran considers that sense should not only have function to absorb information and form knowledge, but also have function to form a conviction in terms of application. Therefore, from the three classification of sense mentioned in Al-Quran, in this context the writer will limit the investigation towards the sense of heart and tongue as part of nobility, which is considered valuable for human compared to other creatures because these senses are two sides of differentiators and links to recognize The Creator.